Haematological and biochemical alterations induced by sodium metavanadate toxicity in male Wistar rats - Ogechukwu G. ONUOHA; Bruno C. CHINKO (Notulae Scientia Biologicae)
Sodium metavanadate (SMV) is an inorganic compound that can enter the human body through multiple pathways, including inhalation, ingestion, dermal absorption, or intentional consumption. The present study evaluated the toxicity profile of SVM and its impact on haematological and biochemical parameters using Wistar rat models. Ten (10) healthy male mice (20-30 g) and twenty (20) male Wistar rats (180-200 g) were used for acute toxicity and experimental studies, respectively. The median lethal dose (LD₅₀) of sodium metavanadate (SMV) was determined using Lorke’s method. The twenty (20) male Wistar rats were randomly assigned into four (4) groups (n = 5 per group). Group I served as the control and received tap water, while Groups II, III, and IV were administered 7.5, 15, and 30 mg/kg of SMV, respectively via oral gavage for twenty-eight (28) days. Blood samples were collected for haematological and biochemical analysis following standard protocols. Also, Liver tissue samples were harvested and analysed histologically to assess structural alterations. The LD₅₀ of SMV was determined to be 80 mg/kg. The findings from this study indicate that SMV exposure resulted in a significant decrease in superoxide dismutase, catalase, glutathione, plasma albumin, packed cell volume, haemoglobin concentration, red blood cells, white blood cells, and lymphocyte counts in the experimental groups compared to the control (p < 0.05). Conversely, a significant increase was observed in the mean levels of malondialdehyde, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and total protein among the experimental animals relative to the control (p<0.05). Histopathological analysis of liver tissue further revealed pronounced Kupffer cell hypertrophy, sinusoidal congestion, and disruption of hepatic architecture. Evidence from this study suggests that SMV exposure may induce anaemia and immunosuppression by disrupting red and white blood cell indices. This effect is likely mediated through increased oxidative stress, which contributes to hepatotoxicity and structural alterations in liver cytoarchitecture.